Managing flows during mega-events: taking account of internal and external flows in public order policing operations. Issue 3 (3rd July 2017) - Whelan, Chad; Molnar, Adam
ABSTRACT: The article examines the configurations and organisational dynamics of policing mega-events through the metaphor of 'flows'. Using the Brisbane 2014 Group of 20 Summit (G20) as an explorative case study, we suggest that the metaphor of flows may not only hold value with regard to understanding how objects of policing are rendered visible and manageable, but also how it might enable us to take stock of internal flows of data, information and intelligence within public order policing operations. We examine how police pursued their goal of containing and controlling protest flows as well as managing rapid intra- and inter-organisational flows. In particular, we examine how police and security actors designed what we call 'flow-based' architectures and the underlying organisational and situational contingencies shaping how these structures and systems form and function. The article concludes by calling for greater attention on internal dynamics of policing operations which, we argue, can potentially be advanced by drawing on the metaphor of flows.